Інформаційно-аналітичне забезпечення управління ризиками господарської діяльності підприємств зернопродуктового підкомплексу - Нестеренко, Світлана Анатоліївна; Нестеренко, Светлана Анатольевна; Nesterenko, Svitlana; Мартинова, Л. В.; Мартынова, Л. В.; Martynova, L. (My University, 2018)
UK: У статті розглянуто сутність, значення та проблеми інформаційно-аналітичного забезпечення управління ризиками господарської діяльності підприємств зернопродуктового підкомплексу в контексті інформаційної економіки на рівні держави, агропромислової галузі та окремого підприємства, а також розроблена модель інформаційно-аналітичного забезпечення в контексті управління ризиками господарської діяльності підприємства зернопродуктового підкомплексу. EN: In the conditions of expansion of integration and globalization processes in world economy information and information resources becomes the main resource. The lack of full and reliable information or ignoring by her subjects of managing at adoption of certain economic decisions at the microlevel can result in bankruptcy, at the macrolevel – in crisis state as separately taken branch, and economy in general. This results from the fact that information has properties to eliminate uncertainty, and, therefore, and the related situation of risk In such conditions the special relevance is acquired by a system research of problems of formation of information and analytical basis of risk management of economic activity at the enterprises of the grain product subcomplex.
Information and analytical ensuring risk management of economic activity of the enterprises of the grain product subcomplex
Keywords: інформація; релевантність інформації; інформаційна економіка; аналітична інформація; управлінська інформація; інформаційно-аналітичне забезпечення; модель інформаційно-аналітичного забезпечення; information; relevance of information; information economy; analytical information; administrative information; information and analytical providing; model of information and analytical providing